Civil society in the context of globalization - Cortez Zambrano, Sonia (University Santo Tomás, Bogotá, 2016)
This article seeks to provide a simple approach to the concept of a Civil Society, its activities and performance in the context of globalizing processes, the impact of their business from the perspective of democracy and politics, and its efficiency as a global partner of the state, reinforcing of democracy and human rights defender.